The role of Islamic corporate governance in Islamic social reporting: evidence from global Islamic banks - Yusuf Faisal; Qonitatun Luthfiyah; Junainah Jaidi; Ibrahim Ibrahim; Egi Gumala Sari (Universitas Islam Negeri Walisongo Semarang, 2026)
Purpose - This study aims to examine the relationship between Investment Account Holder, Non-Performing Financing, and Islamic Intellectual Capital on Islamic Social Reporting with Islamic Corporate Governance as a moderating variable. Method - This study uses quantitative data, with a sample of the 10 largest Islamic banks in the world for the period 2018-2024. The analysis technique used to test the hypothesis is multiple regression analysis using e-views 9 software. Result - The results show that Investment Account Holder, Non-Performing Financing, and Islamic Corporate Governance do not significantly affect Islamic Social Reporting. In contrast, Islamic Intellectual Capital has a significant positive effect on Islamic Social Reporting. Additionally, Islamic Corporate Governance moderates the effects of Non-Performing Financing and Islamic Intellectual Capital on Islamic Social Reporting. However, it does not moderate the effect of Investment Account Holder on Islamic Social Reporting. Implication - Islamic banks are advised to enhance intellectual capital and governance to improve social reporting. Originality - This study examines Islamic Social Reporting in the world’s 10 largest Islamic banks by analyzing the roles of Investment Account Holders, Non-Performing Financing, Islamic Intellectual Capital, and Islamic Corporate Governance as a moderating variable.